Analyses of Plane Stress Discontinuity Lines Systems in Oyane Porous Media - Bodaszewski, W. (Engineering Transactions, 2005)
The paper presents the results of numerical analyses of certain properties of plane stress discontinuity lines systems, which are specific for the Oyane condition, and do not appear when one assumes other yield conditions, such as Huber-Mises or Tresca conditions. The results have been obtained by applying general algorithms that do not require for-emulating any individual relationships. The algorithms aid solving problems for any boundary conditions, of practically any type, which can be met in the problems of construction of dis-continuous statically admissible fields, mainly the limit fields. In the assumed formulation, the solution consists in finding initially the fields arising around isolated nodes of stress discontinuity lines, and then integrating the fields into two-dimensional complex fields. Application of these algorithms makes it possible to quickly find all the existing solutions of the stress discontinuity lines around the nodes, at the same time eliminating the need of forecasting (guessing the solution), which until recently was the main difficulty in solving each new complex field. Physical justification of the Oyane condition is beyond the scope of this work.